Faculty perceptions of faculty development programs in Egyptian universities: An exploratory study - Eldebecky, Noran Ali (AUC Knowledge Fountain, 2017)
Faculty members teaching in the 21st century face pressing challenges of accelerated advancement in their disciplines, pedagogy, and technology. Furthermore, they face a different student body that is demanding better quality education. With these challenges, come the myriad roles of faculty in teaching, research and community service. To navigate successfully between these three pillars and to face the 21st century challenges, faculty development comprehensive initiatives are needed. In Egypt, faculty development started systematically only at the beginning of the 21st century. Thus, it is important to explore the effectiveness of faculty development initiatives from faculty's perspectives. As such, the purpose of this phenomenological exploratory qualitative study is to explore faculty personnel's perceptions of comprehensive faculty development initiatives offered by Egyptian universities inside their premises for faculty professional development. The sample included faculty members from one public university and one private, in addition to faculty developers and the director of the center of learning and teaching in the private university. The main instrument was semi-structure interviews with all participants, in addition to documents from the public university website. Thematic analysis was used for data analysis with the help of NVIVO@11 software. The main results show that faculty members had different perceptions regarding formal faculty development initiatives in their universities that could be grouped in four themes: benefits, motivations and feelings, challenges, and needs. The first theme included academic benefit, through which faculty changed their teaching methods based on faculty development. The second benefit is social, through which faculty shared experiences with colleagues from other disciplines. Faculty also stated two feelings which are frustration from the current faculty development initiatives and some extrinsic motivations that could help them attend more initiatives. Faculty members also reported some challenges that undermine the effectiveness of formal faculty development initiatives. The first challenge reported by participants in the two universities is the one-size-fits-all system. The second challenge, reported only by the public university was organizational bureaucracy. The third challenge was faulty time. The last challenge was having mandatory workshops. Furthermore, faculty members indicated their needs to have a better faculty development experience: first a need for more variety of topics; second more practical workshops; third a need for a bottom up approach for faculty development; and finally a need for more discipline specific workshops. However, each university had its specific subthemes. In the private university all faculty developers' perceptions generally reflected their role as that of pedagogical guidance and support to faculty. This role is clear from the four themes emerging from the data which are: needs assessment for faculty's needs, motivations for better faculty development experience, enhancing teaching and learning through experiential learning, and extended pedagogical support. Finally, the director of the CLT perceptions were very similar to the faculty developers' perceptions. She perceived the CLT role as that of pedagogical support for faculty. Her perceptions can be grouped into four themes: extended pedagogical support, assessment of success, and motivations needed for better faculty development experience. Implications mentioned can guide future faculty development initiatives to better meet faculty's needs.